A Systematic Review and Meta-analysis of Peri-Procedural Outcomes in Patients Undergoing Carotid Interventions Following Thrombolysis. (September 2021) - Kakkos, Stavros K.; Vega de Ceniga, Melina; Naylor, Ross
Abstract : Objective: To evaluate the safety of carotid artery stenting (CAS) and carotid endarterectomy (CEA) after thrombolytic therapy (TT). Data sources: Medline, Scopus, and Cochrane databases. Review Methods: Systematic review and meta-analysis of studies involving patients who underwent CEA/CAS after TT. Results: In 25 studies ( n  = 147 810 patients), 2 557 underwent CEA ( n  = 2 076) or CAS ( n  = 481) following TT. After CEA, the pooled peri-procedural stroke/death rate was 5.2% (95% confidence interval [CI] 3.3 – 7.5) and intracranial haemorrhage (ICH) was 3.4% (95% CI 1.7 – 5.6). After CAS, the pooled peri-procedural stroke/death rate was 14.9% (95% CI 11.9 – 18.2) and ICH was 5.5% (95% CI 3.7 – 7.7). In case control studies comparing CEA outcomes in patients receiving TT vs. no TT, peri-procedural death/stroke was non-significantly higher after TT (4.3% vs. 1.5%; odds ratio [OR] 2.34, 95% CI 0.74 – 7.47), but ICH was significantly higher after TT (2.2% vs. 0.12%; OR 7.82, 95% CI 4.07 – 15.02), as was local haematoma formation (3.6% vs. 2.26%; OR 1.17, 95% CI 1.17 – 2.33). In case control studies comparing CAS outcomes in patients receiving TT vs. no TT, peri-procedural stroke/death was significantly higher after TT (5.2% vs. 1.5%; OR 8.49, 95% CI 2.12 – 33.95) as was ICH (5.4% vs. 0.7%; OR 7.48, 95% CI 4.69 – 11.92). Meta-regression analysis demonstrated an inverse association between the time interval from intravenous (IV) TT to undergoing CEA and the risk of peri-procedural stroke/death ( p = .032). Peri-operative stroke/death was 13.0% when CEA was performed three days after TT and 10.6% when performed four days after TT, with the risk reducing to within the currently accepted 6% threshold after six-seven days had elapsed. Conclusion: Peri-procedural ICH and local haematoma were significantly more frequent in patients undergoing CEA after TT ( vs. no TT), although there were no randomised comparisons. Peri-procedural hazards were also significantly higher for CAS after TT. The inverse relationship between timing to CEA and peri-procedural stroke/death mandates careful patient selection and suggests that it may be safer to defer CEA for six-seven days after TT.